The Essentials of American History / Second Edition - Alfred A. Knopf; Brownlee W. Elliot; Current Richard N; Freidel Frank; Williams T. Harry (1976)
Englishmen Become Americans and Gain Their Independence, The Young Republic Makes a Successful Start Under a New Constitution, Sectionalism Contends with Nationalism as the Country Expands, North and South Separate Fight and Rejoin while the Slaves Gain Partial Freedom, Modern America Emerges, From Total War Through Depression, Another Foreign Crusade with Mixed Results, Man Visits Other Worlds Before He Puts His Own in Order, Index.
Englishmen Become Americans and Gain Their Independence, The Young Republic Makes a Successful Start Under a New Constitution, Sectionalism Contends with Nationalism as the Country Expands, North and South Separate Fight and Rejoin while the Slaves Gain Partial Freedom, Modern America Emerges, From Total War Through Depression, Another Foreign Crusade with Mixed Results, Man Visits Other Worlds Before He Puts His Own in Order, Index.